ASPECTS OF MULTICOMPONENT THERAPY AND PERIOPERATIVE TACTICS IN A PATIENT WITH ATRIAL FIBRILLATION RECEIVING RIVAROXABAN THERAPY. CLINICAL OBSERVATION - O. A. Zemlyanskaya; E. S. Kropacheva (Атеротромбоз, 2019)
The use of modern oral anticoagulants is associated with a significant reduction in the risk of stroke and systemic embolism in patients with atrial fibrillation, and thus with an increase in the life expectancy of patients. That is why multicomponent therapy and perioperative tactics are actual during prolonged anticoagulation, the aspects of which seem to be one of the most difficult from the practical point of view. This clinical observation is an illustration of the management of a patient with atrial fibrillation at high thromboembolic risk who is receiving Rivaroxaban therapy and who has indications for catheter ablation and multicomponent antithrombotic therapy.